The psychological impact of COVID-19 disease on nurses in two tertiary healthcare centers in Akwa Ibom State, Nigeria - Jombo, Henry E.; Ekwere, Timothy Amos; Umoh, Victor A.; Ndionuka, Nkemakolam F.; Akpan, Effiong E. (International Journal Of Community Medicine And Public Health, 2021)
Background: The onset of COVID-19 disease pandemic worldwide has been associated with a high level of psychological distress. Health workers are amongst the high-risk groups for contracting COVID-19 and may be particularly vulnerable to a variety of mental health problems. This study was conducted to determine the psychological impact of the pandemic on mental well-being of Nigerian nurses who are among the frontline health workers in the fight against the disease. Methods: This was a cross-sectional study conducted on a sample of nurses in two tertiary healthcare setting. A simple random sample of 111 nurses completed the general healthcare questionnaire (GHQ 12). Results: The mean age of respondents was 36.86±8.2 years, consisting of 38.7% males and 61.3% females. The prevalence of psychological distress was 64.9%. Females had significantly higher psychological distress than males (p=0.003). Also, respondents performing duties in COVID-19 ICU hosting institution had significantly higher distress score than those from non COVID-19 hosting centre (p=0.02). Psychological distress was also significantly higher for respondents with a history of exposure to suspected (p=0.001) or confirmed cases (p<0.001). Formal infection prevention training was a protective factor for the development of psychological stress (p=0.002). Conclusions: A large proportion of nursing staffs have a high level of psychological distress during the ongoing COVID-19 pandemic. Mental health interventions may be required to mitigate mental health risks in these health workers.